The Influence Of Intellectual Capital On Financial Performance In The Banking Sector Listed On The Indonesia Stock Exchange - Ahmad Sahara; Marlina Widiyanti; Mu'izzuddin Mu'izzuddin; Mukhtaruddin Mukhtaruddin (Al-Makki Publisher, 2024)
This study aims to analyze the influence of intellectual capital on financial performance in the banking sector listed on the Indonesia Stock Exchange (IDX), with Return on Assets (ROA) as the leading indicator. Intellectual capital is measured using Value Added Intellectual Coefficient (VAIC), which consists of three components: Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), and Structural Capital Value Added (STVA). The quantitative method is used with secondary data from the annual financial statements of banking companies for the period 2018–2022. The sample consisted of 15 banks selected through the purposive sampling technique. The results of the regression analysis show that VACA, VAHU, and STVA have a significant and positive influence on ROA, which shows that investment in intellectual capital plays a vital role in improving bank profitability. These findings have implications that banks can prioritize human and structural capital development to enhance financial performance. The recommendations of this study include further exploration of the long-term impact of intellectual capital on various economic conditions.